Institutional Entrepreneurs as Change Agents in Rural Peripheral Regions? - Leick, Birgit (Verl. der Österreichischen Akademie der Wissenschaften, 2020)
This paper emphasises a different perspective on entrepreneurship for regional contexts that goes to the core of the question of who and what an entrepreneur can be and how entrepreneurs contribute to regional economic development. The answer that this paper offers focuses on institutional entrepreneurship, which encompasses the idea that there is a wider field of agents in regions than owner-managers of companies. It is argued that manifold actors can show entrepreneurial behaviour and bring about a disruptive transformation of the regional economy. With new combinations of resources, knowledge and ideas, but also with their capabilities to strategize, mobilise and lead collective action, institutional entrepreneurs represent such change agents that can support economic development notably in rural-peripheral regions.

Der Beitrag greift den Begriff des "Institutional Entrepreneurship" auf und diskutiert, inwiefern öffentliche Akteure als Agenten ökonomischen Wandels auftreten können.
Keywords: Regionalentwicklung; Regionalwirtschaft; Periphere Region; Ländlicher Raum; Unternehmensgründung; Institution; Akteur; Entrepreneurship; Wirtschaftswandel